PENGARUH MEKANISME CORPORATE GOVERNANCE (GCG) TERHADAP NON PERFORMING LOAN (NPL) PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zoriton, Zoriton; Husaini, Husaini; Usman, Darman (UNIB Press, 2021)
This study was conducted with the aim of empirically testing the analysis of the influence of internal audit, managerial ownership, independent commissioners, and audit committees on Non-Performing Loans (NPLs) on banking companies listed on the Indonesia Stock Exchange (IDX). This type of research is causal research, namely this study looks for a causal relationship between the independent variable and the dependent variable. The population in this study were all banking companies listed on the Indonesia Stock Exchange in 2011-2018, namely 45 banking companies. The sample in this study was obtained by the purpose sampling method. Based on existing criteria, 31 banking companies were obtained. Hypothesis testing is done by multiple linear regression analysis.The results of the internal audit variable, managerial ownership, independent commissioner research have a negative effect on Non-Performing Loans (NPL) on banking companies listed on the Indonesia Stock Exchange (BEI) in 2011-2018. The auditing committee variable does not affect the Non Performing Loans (NPL) of banking companies listed on the Indonesia Stock Exchange (BEI) in 2011-2018